2017
DOI: 10.1038/ismej.2017.102
|View full text |Cite
|
Sign up to set email alerts
|

Novel chaperonins are prevalent in the virioplankton and demonstrate links to viral biology and ecology

Abstract: Chaperonins are protein-folding machinery found in all cellular life. Chaperonin genes have been documented within a few viruses, yet, surprisingly, analysis of metagenome sequence data indicated that chaperonin-carrying viruses are common and geographically widespread in marine ecosystems. Also unexpected was the discovery of viral chaperonin sequences related to thermosome proteins of archaea, indicating the presence of virioplankton populations infecting marine archaeal hosts. Virioplankton large subunit ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 64 publications
1
20
0
Order By: Relevance
“…"gene signatures") encoding the above mentioned capsid protein (Fig. 2c), previously characterized to be the most abundant in marine viral proteomes [19], a terminase (TerL), and a chaperonin Gro-Es, recently described to be widespread in marine virosphere and always placed upstream from capsid genes [25], as found in this case. Furthermore, the uncultured pelagiphages in SAG AG-470-G06 and AG-422-I02 had a gene annotated as "genome maintenance exonuclease 1" at JGI-IMG, that was also present in the bacterial genome of 18 different Pelagibacter SAGs ( Supplementary Table 8), including SAG MED40; all of them from oligotrophic environments.…”
supporting
confidence: 63%
“…"gene signatures") encoding the above mentioned capsid protein (Fig. 2c), previously characterized to be the most abundant in marine viral proteomes [19], a terminase (TerL), and a chaperonin Gro-Es, recently described to be widespread in marine virosphere and always placed upstream from capsid genes [25], as found in this case. Furthermore, the uncultured pelagiphages in SAG AG-470-G06 and AG-422-I02 had a gene annotated as "genome maintenance exonuclease 1" at JGI-IMG, that was also present in the bacterial genome of 18 different Pelagibacter SAGs ( Supplementary Table 8), including SAG MED40; all of them from oligotrophic environments.…”
supporting
confidence: 63%
“…During phage replication, chaperonin is usually supplied from the host and involved in the generation of phage particles 35 . However, recent metagenomic data indicated that chaperonin-encoding viruses are more common than previously thought and geographically widespread in marine ecosystems 36 , 37 . By encoding its own chaperonin, XacN1 virion assembly process might not be totally dependent on the host chaperonin machinery.…”
Section: Resultsmentioning
confidence: 99%
“…each subunit in one ring interacts with two subunits in the opposing ring, whereas the subunits in group II chaperonins interact in a one to one fashion. 7 of ɸEL and GroEL ( 0.2 µM tetradecamer) in the absence or presence of GroES (0.4 µM heptamer) or 0.8 µM denatured DM-MBP (diluted from 6M GuHCl, final ~20 mM) were performed in LS or HS buffer and in presence of 1 mM ATP. The ATPase activity of ɸEL (0.2 µM tetradecamer) was also measured with increasing concentrations of GroES.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, ɸEL may represent an evolutionary more ancient chaperonin prior to acquisition of the encapsulation mechanism.4 Evolutionary more distant chaperonin homologs were discovered in the genomes of bacteriophages. While many phages encode only a GroES homolog that cooperates with the host GroEL [6], some have both GroEL and GroES homologs and few encode only a GroEL-like chaperonin [7]. The latter group includes the protein gp146 from the bacteriophage EL of Pseudomonas aeruginosa [8,9], henceforth referred to as ɸEL.…”
mentioning
confidence: 99%